Macrofinancial Linkages and Growth at Risk in the Dominican Republic - Bespalova, Olga (IMF Working Papers; Working Paper, 2019)
This paper uses the Growth-at-Risk (GaR) methodology to examine how macrofinancial conditions affect the growth outlook and its probability distribution. Using this approach, we evaluate risks to GDP growth in the Dominican Republic using quarterly data for 1996-2018. We group macrofinancial conditions in five principal determinants, based on 32 indicators. The Dominican Republic's growth distribution appears most vulnerable to negative shocks to domestic financial conditions, domestic leverage, domestic demand, and external demand, with additional repercussions from the external cost of borrowing in the longer run. Our findings show that domestic monetary policy plays a particularly important role in reducing growth vulnerabilities when the economy is weak.